Evaluasi Penerapan Sistem Pengendalian Intern Pemerintah (SPIP) pada Satuan Kerja X - Riszka Indriani; Dodik Siswantoro (Politeknik Ganesha Medan, 2023)
This study was performed to evaluate the implementation of Government Internal Control System (SPIP) at Government Institution X and develop suggestions for internal control flaws. The results of the 2020 Supreme Audit Agency (BPK) examination showed that of the 11 findings obtained, 9 were findings of deficiencies in the internal control system. This reflects that the internal control conditions in this working unit are still not optimal. Furthermore, there were repeated findings in the implementation of assistance distribution which is a national priority program. This has the potential to hamper the attainment of the national priority program objectives and hinder the equitable distribution of education in Indonesia. Government Institution X is an institution that manages many national priority programs, so it is important for this institution to improve internal control to maintain accountability and minimize findings related to aid distribution. This research is qualitative research and uses a case study strategy. Data were obtained through documentation, interviews, and observations. The results of this study show that SPIP at Government Institution X has been running well, but still needs improvement in several aspects. Strengthening is still needed in the internal control monitoring element where the evaluation results have not been fully followed up, so the improvement process is hampered.